Evaluasi Kadar Gula Darah Pasien Berdasarkan Kajian Usia dan Komplikasi Penyakit pada Pasien Diabetes Mellitus Tipe-2 di Puskesmas Jetis 1 Bantul Periode September–November 2019 - Reyaldi, Caesar Bagus; -, Akrom; Candradewi, Susan Fitria (Jurnal Farmasi Udayana; Vol. 10, No 2, Tahun 2021DO - 10.24843/JFU.2021.v10.i02.p04, 2021)
Diabetes mellitus is a chronic disease which causes blood sugar levels increase. Increasing age affects performance of body organs function against insulin which leads to fluctuations in blood sugar. Decreased performance of body functions affects balance of other body functions which can cause complications. The research objective was to determine and evaluate blood sugar levels based on age and disease complications. The research design used was analytic observational research. Data were collected retrospectively from September - November 2019. Univariate analysis is used to analyze basic characteristics of research variables. Bivariate analysis was used to determine differences in patient blood sugar based on age and disease complications. The statistical test used is the Kruskal Wallis test. The results showed blood sugar levels based on the age obtained is 0.289; 0,242; 0,150; 0,658; 0,557; 0.711 (p > 0.05); 0.040 (p<0.05). Test results based on disease complications were 0.317; 0.626; 0.121; 0.932; 0.658; 0.214; 0.104 (p > 0.05).The conclusion is there is no significant difference in blood sugar levels of patients based on age and complications of the disease in the period September 2019 – November 2019. Diabetes mellitus patients had controlled blood sugar levels based on age and disease complications